2004
DOI: 10.1002/bit.20160
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating chondrocytes in degrading PEG hydrogels with high modulus: Engineering gel structural changes to facilitate cartilaginous tissue production

Abstract: A major challenge when designing cell scaffolds for chondrocyte delivery in vivo is creating scaffolds with sufficient mechanical properties to restore initial function while simultaneously controlling temporal changes in the gel structure to facilitate tissue formation. To address this design challenge, degradable photocrosslinked hydrogels based on poly(ethylene glycol) were investigated. To alter the gel's initial mechanical properties, hydrogels were fabricated by varying the initial macromer concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
258
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(263 citation statements)
references
References 23 publications
(29 reference statements)
4
258
0
1
Order By: Relevance
“…12,14 Those studies demonstrated that measures of chondrogenesis increased with decreasing cross-link density. Other work 15 investigating the effects of the modulus of hydrogels on encapsulated chondrocytes found no difference in the GAG contents between the gels with the highest and lowest stiffness (despite the 10-fold difference in modulus). The facts that even the lowest modulus hydrogel may have been stiff enough to resist contraction and that the cells may not have been able to sufficiently bind to the hydrogel to exert a contractile force, may in part explain why there was no effect observed between the modulus and GAG, relative to the hypothesis of the present work.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…12,14 Those studies demonstrated that measures of chondrogenesis increased with decreasing cross-link density. Other work 15 investigating the effects of the modulus of hydrogels on encapsulated chondrocytes found no difference in the GAG contents between the gels with the highest and lowest stiffness (despite the 10-fold difference in modulus). The facts that even the lowest modulus hydrogel may have been stiff enough to resist contraction and that the cells may not have been able to sufficiently bind to the hydrogel to exert a contractile force, may in part explain why there was no effect observed between the modulus and GAG, relative to the hypothesis of the present work.…”
mentioning
confidence: 83%
“…A related limitation is that it was not possible from this study to extrapolate a correlation of the MSC chondrogenic differentiation with select initial mechanical properties (e.g., compressive modulus) of the porous collagen scaffolds, to parallel work demonstrating the effect of substrate rigidity on the differentiation of MSCs in monolayer culture, 34 and prior work 15 investigating the effects of the modulus of hydrogels on encapsulated chondrocytes. Previous studies have reported the compressive modulus of collagen scaffolds which have undergone various types of cross-link treatments, [11][12][13] but these treatments also affect degradation rate; the difficulties in distinguishing the relative effects of the type and degree of cross-linking on enzymatic degradation of collagen scaffolds has been previously noted.…”
Section: Cross-linking Affects Cellular Condensation and Chondrogenesismentioning
confidence: 99%
“…Proper selection of the macromolecular precursors used to synthesize the gels allows the initial mechanical properties, degradation behavior and biological activity of the network to be selectively tuned for a variety of applications. Previous work has demonstrated that network degradation can be used to control drug release temporally and influence tissue formation [1,2,6,9,11,14,20,21,[25][26][27][28][29]. Degradation in covalently crosslinked polymeric biomaterials has been achieved through hydrolytic cleavage of esters and anhydrides and also through enzymatically induced cleavage of select peptide sequences that have been incorporated into the material [2,22,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In tissue engineering, encapsulating and organizing cells within a three-dimensional hydrogel scaffold can direct the formation of desired tissue through the presentation of specific signaling cues 1,2 . Recently, implantation of a cell-laden hydrogel scaffold has been developed as an alternative and appealing approach for controlled, sustainable in vivo growth factor delivery 3 .…”
Section: Introductionmentioning
confidence: 99%